PENERAPAN METODE PROBLEM SOLVING DALAM UPAYA MENINGKATKAN PEMAHAMAN KONSEP ALJABAR PADA SISWA KELAS VII MTS DAARUL MUTTAQIEN - Rosyiana Turrizkiyah; Rukmono Budi Utomo (AlphaMath : Journal of Mathematics Education, 2016)
This study starts from the emergence of problems experienced directly by the author at the time of learning as the low student understanding of algebra, it is severe to the understanding of concepts in mathematics, because the concept of algebra can solve problems related to everyday life. In an effort to provide insight to student approach method writer chose is a Class Action Research (CAR), which combines methods poblem solving tries to study and reflect on a learning model with the aim of increasing understanding of the quality (both process and product) a lesson. Keyword: Problem solving, emergency, Class Action Research